Entry barriers and “Glass Roof” in University Management in Colombia - Bedoya Dorado, Cristian; García-Solarte, Mónica; Peña-Zúñiga, Juan Sebastián; Piñeros Buriticá, Steven Alejandro (Cuadernos de Administración, 2019)
Management in the context of higher education has been characterized by the predominance of male participation, mainly in senior management positions. As a result, women’s low participation is mainly concentrated in lower management positions, and their chances of escalating hierarchical positions are mediated by various factors ranging from subjective to socially naturalized. The objective of this research is to analyze the barriers women face to enter and escalate positions in university management in Colombia. Under a qualitative design, 26 semi-structured interviews were applied to university managers from different institutions of higher education in Colombia. The transcripts were analyzed using discourse analysis through three categories: individual, internal, and external barriers of the university. It was found that women face entry and promotion barriers marked by experiences, and conditions of inequality and discrimination in a male-dominated context. These barriers are conditioned by personal elements, organizational culture, and the social role of women. In addition, women’s trajectories involve mediation between professional development and family life. The study reveals experiences that contribute to understanding the research phenomenon from the webbing of senses and meanings. It is posited that the “glass ceiling” is mediated by variables in the internal order, and by the relationship between universities and their context.